2y+(5-7y)-9-(3y-2)=

Simple and best practice solution for 2y+(5-7y)-9-(3y-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y+(5-7y)-9-(3y-2)= equation:


Simplifying
2y + (5 + -7y) + -9 + -1(3y + -2) = 0

Remove parenthesis around (5 + -7y)
2y + 5 + -7y + -9 + -1(3y + -2) = 0

Reorder the terms:
2y + 5 + -7y + -9 + -1(-2 + 3y) = 0
2y + 5 + -7y + -9 + (-2 * -1 + 3y * -1) = 0
2y + 5 + -7y + -9 + (2 + -3y) = 0

Reorder the terms:
5 + -9 + 2 + 2y + -7y + -3y = 0

Combine like terms: 5 + -9 = -4
-4 + 2 + 2y + -7y + -3y = 0

Combine like terms: -4 + 2 = -2
-2 + 2y + -7y + -3y = 0

Combine like terms: 2y + -7y = -5y
-2 + -5y + -3y = 0

Combine like terms: -5y + -3y = -8y
-2 + -8y = 0

Solving
-2 + -8y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + -8y = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -8y = 0 + 2
-8y = 0 + 2

Combine like terms: 0 + 2 = 2
-8y = 2

Divide each side by '-8'.
y = -0.25

Simplifying
y = -0.25

See similar equations:

| f(x)=x^3-2.25x^2-3x | | x+2*4=4 | | 427xX=X | | x+0y=4 | | Y+3z=10 | | x-6=-31 | | x(x+3)(x+3)=x(x-3)(x+3) | | 6-4(x+5)=-16 | | K=9r-a | | 2x^2+y^2=17 | | -4(y+5)=8-6(y+7) | | 7y-(8y+9)=10 | | 2x^4+20x^2+18=0 | | 5x=3x-4x+10+2 | | -4(-2)(-5)= | | 4+5=445 | | [(x^3+4X)(6X+2)]+[(3X^2+2X-5)(3X^2+4)]= | | 4+4=445 | | X=(x+500)+4x-1100 | | 2ln(2x)=4-ln(25) | | H=-16x^2+108x+160 | | X=-16x^2+108x+160 | | 5a+4c=7549.47 | | X=2x^2-1600 | | 4x+3=5-2x | | 5a+4c=100 | | 6.1x-3.5=20.9 | | X+3x+5=117 | | 18x+1=5x+2 | | 5(b-9)=12 | | x^2+6x+9+16=x^2+10x+25 | | 7x=5-4(1-3x) |

Equations solver categories